1996
DOI: 10.1192/bjp.169.3.348
|View full text |Cite
|
Sign up to set email alerts
|

Single Photon Emission Computerised Tomography in Chronic Alcoholism

Abstract: Patients with ASP are more sensitive to toxic effects of alcohol. Alternatively chronic alcoholism leads to frontal lobe dysfunction recognised as ASP in the clinical setting.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
26
1

Year Published

1999
1999
2018
2018

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 100 publications
(29 citation statements)
references
References 16 publications
2
26
1
Order By: Relevance
“…This dose-response relationship is consistent with the majority of perfusion studies in ALC (Gazdzinski et al, 2006; Kuruoglu et al, 1996; Melgaard et al, 1990; Nicolas et al, 1993) but not all (Mon et al, 2009), and congruent with the apparently greater vulnerability of anterior frontal regions to chronic alcohol consumption. In sALC but not in sPSU, greater smoking severity related to lower perfusion in parietal, temporal and subcortical regions, suggesting susceptibility of select regions to cigarette smoking effects (Durazzo et al, 2014a) and consistent with healthy (elderly) smokers showing greater rates of atrophy in select regions than nonsmokers (Durazzo et al, 2012a).…”
Section: Discussionsupporting
confidence: 83%
See 1 more Smart Citation
“…This dose-response relationship is consistent with the majority of perfusion studies in ALC (Gazdzinski et al, 2006; Kuruoglu et al, 1996; Melgaard et al, 1990; Nicolas et al, 1993) but not all (Mon et al, 2009), and congruent with the apparently greater vulnerability of anterior frontal regions to chronic alcohol consumption. In sALC but not in sPSU, greater smoking severity related to lower perfusion in parietal, temporal and subcortical regions, suggesting susceptibility of select regions to cigarette smoking effects (Durazzo et al, 2014a) and consistent with healthy (elderly) smokers showing greater rates of atrophy in select regions than nonsmokers (Durazzo et al, 2012a).…”
Section: Discussionsupporting
confidence: 83%
“…Similarly, glucose metabolism is decreased in frontal regions of ALC and cocaine dependent individuals (Adams et al, 1993; Dao-Castellana et al, 1998; Volkow et al, 1992a, 1992b, 1994; Wang et al, 1993). In alcoholism, both chronic alcohol and tobacco use are associated with altered perfusion: higher alcohol consumption is associated with lower frontal and parietal perfusion (Kuruoglu et al, 1996; Melgaard et al, 1990; Nicolas et al, 1993), and greater cigarette smoking severity is associated with lower frontal and/or parietal perfusion in smoking ALC (sALC) (Gazdzinski et al, 2006; Mon et al, 2009), but see (Sullivan et al, 2013). These reductions in regional blood flow and glucose metabolism are of functional importance as they are associated with relapse to drinking within the first year after treatment (Durazzo et al, 2010a) and poorer neurocognition in cocaine dependence (Browndyke et al, 2004; Goldstein et al, 2004, 2001; review by Hanlon et al, 2013) and in alcohol dependence (Adams et al, 1993; Dao-Castellana et al, 1998; Goldstein et al, 2004; Melgaard et al, 1990; Nicolas et al, 1993; Wang et al, 1993), although with some contradictions (Demir et al, 2002; Gazdzinski et al, 2006; Mon et al, 2009).…”
Section: Introductionmentioning
confidence: 99%
“…Overall, the profiles of early-onset patients bore considerable similarity to those of patients with psychopathy or sociopathy ('Conduct Disorder' or 'Antisocial Personality Disorder' , according to DSM-IV nosology 15 ), another early onset disorder characterized by a pervasive disregard for social and moral standards, consistent irresponsibility and a lack of remorse. Psychopathy may be associated with dysfunction in prefrontal regions [16][17][18] , especially in persons without predisposing psychosocial risk factors 18 . Also of note, children with antisocial tendencies have deficiencies of moral reasoning relative to age-matched controls 19,20 , and abnormal psychophysiological arousal and reactivity are found in adults with antisocial behav- Fig.…”
Section: Discussionmentioning
confidence: 99%
“…A comparison of alcohol dependent subjects with healthy controls found that alcoholic subjects with an antisocial personality disorder had significantly greater frontal hypoperfusion than other alcoholic subjects 53. As a group, adolescent and adult psychiatric patients who had physically attacked another person or destroyed property showed significantly decreased prefrontal activity compared with matched, non-aggressive psychiatric patient controls 54.…”
Section: Neuroimaging In Aggressive and Violent Subjectsmentioning
confidence: 98%